PENENTUAN AWAL BULAN HIJRIAH PERSPEKTIF MAZHAB MALIKI - David Wildan; Ahmad Adib Rafiuddin (Tafáqquh: Jurnal Penelitian Dan Kajian Keislaman, 2021)
Abstract: As the month of Ramadan approaches, one of the discussions that will almost certainly become the subject of public discussion is about when to start the fasting month of Ramadan. Muslims seem to be divided in the discourse of the difference between reckoning and rukyah. The Imkanurrukyah method or the visibility of the hilal which is considered capable of being a mediating bridge between the two methods turns out to only apply in a few countries, not all countries are willing to accept these criteria. Countries that use the Maliki School as a reference for Islamic law in the North African region are one of the groups that are quite difficult to accept the criteria for the visibility of the new moon. This paper discusses the legal basis for the use of the rukyah method by the Maliki school and what its implications are for determining the beginning of the lunar month in people who follow this school. After conducting a study of various existing literatures, the argument that was built from the writing of this paper is that the Maliki School does not recognize the reckoning method as one of the methods in determining the beginning of the Hijri month. Furthermore, the monarchical political system adopted by most countries in the region is the reason why in the region there has never been a difference in determining the beginning and end of fasting even though globally their decisions are different from those of other countries and schools. Kata Kunci: Kalender Hijriah, Mazhab Maliki, Rukyah, Hilal.